EFFICACY OF PRISHNAPARNI-BALA-VASA KWATHA IN GARBHAVASTHA JANYA SHOPHA - M, *Shubha; Siddesh, Sunita (AYUSHDHARA, 2015)
Many signs and symptoms produced during pregnancy are caused due to the anatomical and physiological changes in mother and maternal adaptation to these changes. One such symptom which appears physiologically during pregnancy is “Garbhavastha Janya Pada Shopha”. The incidence of oedema in normal healthy pregnant women is reported to be 50-80%. If Pada shopha is ignored and not treated then it acts as a precursor and predisposes to the development of deep-vein thrombosis. Hence emphasis is given for pedal oedema during pregnancy in this study. Early detection and appropriate treatment is the need of the hour to reduce the Pada Shopha and to overcome the complications underlying the Pada Shopha. In Yoga Rathnakara specific treatment for Garbhavastha Janya Shopha is advocated with Prishna Parni-Bala-Vasa Kwatha. Materials and Methods: 30 patients registered and diagnosed as Garbhavastha Janya Shopha (non-pathological mild to moderated pedal oedema) were treated with Prishnaparni-Bala-Vasa Kwatha three times daily for 15 days. Dose -16 ml thrice daily orally. Follow up: On 22thand 29thday. Results: Statistically significant results was seen, for location t=11.0886 and p= <0.0001, circumference at forefoot in right & left leg was t= 8.8039 and p= <0.0001 & at ankle joint in right and left leg was t=6.0990 and p= <0.0001, on bilateral/unilateral oedema was t=8.9303 and p= <0.0001, on grades at forefoot, ankle joint in right and left leg was t= 7.8831 and p=<0.0001, on pitting at forefoot, ankle in right and left leg was t= 7.8831 and p=<0.0001, time of aggravation was t= 8.6509 and p= <0.0001. Conclusion: Hence it can be concluded that Prishnaparni-Bala-Vasa Kwatha is effective in treating non-pathological mild to moderate Garbhavastha Janya Shopha.